The Effect of Shadow and Ball-Passing Training Methods on Forehand Drive Stroke Accuracy in PTM Pade Angen Mataram Table Tennis Athletes - Dwi Ria Silvira; Johan Irmansyah; Supriadin Supriadin (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2026)
This study aims to determine the effect of shadow and ball passing training methods on the accuracy of forehand drive stroke in table tennis athletes of PTM Pade Angen Mataram. The accuracy of the forehand drive is one of the most important basic techniques in the game of table tennis because it plays a role in creating effective attacks and earning points. However, there are still athletes who have difficulty in performing forehand drive shots accurately and consistently. Therefore, effective training methods are needed to improve these abilities. The method used in this study is an experimental method with a pre-test and post-test design. The sample consisted of 10 athletes. The data collection technique uses a forehand drive stroke skill test in table tennis. Based on the analysis using descriptive statistical techniques, the calculated t(H0) value is 10.628, while the t-table value at the significance level of 5% with the degree of freedom (df) = n - 1 = 9 is 2.262. Due to the t-table (10.628 > 2.262), the null hypothesis (H₀) is rejected and the alternative hypothesis (H₁) is accepted. Thus, it can be concluded that there is a significant effect of the shadow and ball feed training methods on the accuracy of forehand drive shots. In other words, shadow and ball pass exercises can improve forehand drive hitting skills in table tennis.